Perceptions of Parental Needs in General Pediatric Inpatient Units: A Comparative Study Between Nurses and Parents in Saudi Arabia - Hawa Alabdulaziz; Malak Alharthi; Sara Alhazmi; Alyaa Hawsawi; Shahad Almuhyawi; Zahra Almalki (Children, 2025)
Introduction: Hospitalization of children creates significant emotional and psychological stress for parents, highlighting the importance of addressing their needs in pediatric care settings. Aims: This study examines the perceptions of both parents and pediatric nurses regarding the needs of hospitalized children. Method: A cross-sectional survey using the validated Needs of Parents of Hospitalized Children (NPQ) was administered to 218 parents and 218 pediatric nurses in four hospitals in Jeddah, Saudi Arabia. Key domains assessed included trust, information, and support. Group differences were evaluated using non-parametric statistical analyses. Results: Trust was prioritized more by parents (83.9%) than nurses (72.4%) (p < 0.05). Both groups deemed information important, but parents (87.2%) rated it as more necessary than nurses (74.1%) (p = 0.02). Parents (79.8%) expressed a greater need for support compared to nurses (67.3%) (p = 0.03). Conclusions: This study identified perceptual differences between parents and nurses regarding trust, communication, and support. Some differences were statistically significant at the p < 0.01 level, while others were suggestive (p-value between 0.01 and 0.05) and require further investigation. These disparities suggest a need to foster mutual understanding and improve communication practices to better align healthcare delivery with family expectations and strengthen family-centered care.